Loneliness, social isolation, cardiovascular disease and mortality: a synthesis of the literature and conceptual framework. (May 2020) - Hodgson, Sam; Watts, Isabella; Fraser, Simon; Roderick, Paul; Dambha-Miller, Hajira
To conduct a systematic review and develop a conceptual framework on the mechanisms linking loneliness, social isolation, health outcomes and mortality. Electronic databases were systematically searched (PubMed, MEDLINE, Scopus and EMBASE) from inception to October 2018 followed by manual searching to identify research on loneliness, social isolation and mortality in adults published in the English language. Articles were assessed for quality and synthesised into a conceptual framework using meta-ethnographical approaches. A total of 122 articles were included. These collated observational designs examining mediators and moderations of the association in addition to qualitative studies exploring potential mechanisms were included. A framework incorporating 18 discrete factors implicated in the association between loneliness, social isolation and mortality was developed. Factors were categorised into societal or individual, and sub-categorised into biological, behavioural and psychological. These findings emphasise the complex multidirectional relationship between loneliness, social isolation and mortality. Our conceptual framework may allow development of more holistic interventions, targeting many of the interdependent factors that contribute to poor outcomes for lonely and socially isolated people.